Introduction of mutual teaching in schools of Cuba, Guatemala and Mexico (2017)
This article presents and describes the itinerary of the arrival of mutual education in Cuba, Guatemala and Mexico, the participation of patriotic societies such as: the Sociedad Económica de los Amigos del País de la Habana, the Real Sociedad Económica de Amantes de la Patria de Guatemala, the Real Junta de Caridad y Sociedad Patriótica para la Buena Educación de la Juventud de Puebla, and some preceptors that impacted and managed to transform the primary education in these countries during the second decade of the 19th. To this end, an epochal documentation follow-up was carried out by contextualizing the actions of the associations and giving prominence to the introduction of the mutual teaching method. The chronology is established to identify where the Lancasterian method was taken from and the first actors who applied it are characterized.